Late initiation of combination antiretroviral therapy in Canada: a call for a national public health strategy to improve engagement in HIV care. Issue 1 (5th October 2015) - Cescon, Angela; Patterson, Sophie; Davey, Colin; Ding, Erin; Raboud, Janet M; Chan, Keith; Loutfy, Mona R; Cooper, Curtis; Burchell, Ann N; Palmer, Alexis K; Tsoukas, Christos; Machouf, Nima; et al.
Abstract : Introduction: Combination antiretroviral therapy (ART) significantly decreases morbidity, mortality and HIV transmission. We aimed to characterize the timing of ART initiation based on CD4 cell count from 2000 to 2012 and identify factors associated with late initiation of treatment. Methods: Participants from the Canadian Observational Cohort (CANOC), a multi‐site cohort of HIV‐positive adults initiating ART naively after 1 January 2000, in three Canadian provinces (British Columbia, Ontario and Québec) were included. Late initiation was defined as a CD4 count <200 cells/mm 3 or an AIDS‐defining illness before ART initiation (baseline). Temporal trends were assessed using the Cochran–Armitage test, and independent correlates of late initiation were identified using logistic regression. Results: In total, 8942 participants (18% female) of median age 40 years (Q1–Q3 33–47) were included. The median baseline CD4 count increased from 190 cells/mm 3 (Q1–Q3 80–320) in 2000 to 360 cells/mm 3 (Q1–Q3 220–490) in 2012 ( p <0.001). Overall, 4274 participants (48%) initiated ART with a CD4 count <200 cells/mm 3 or AIDS‐defining illness. Late initiation was more common among women, non‐MSM, older individuals, participants from Ontario and BC (vs. Québec), persons with injection drug use (IDU) history and individuals starting ART in earlier calendar years. In sub‐analysis exploring recent (2008 to 2012) predictors using an updated CD4 criterion (<350 cells/mm 3 ), IDU and residence in BC (vs. Québec) were no longer significant correlates of late initiation. Conclusions: This analysis documents increasing baseline CD4 counts over time among Canadians initiating ART. However, CD4 counts at ART initiation remain below contemporary treatment guidelines, highlighting the need for strategies to improve earlier engagement in HIV care.